2019
DOI: 10.1038/s41377-019-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-in-the-lens architecture for a miniature high-NA laser scanning microscope

Abstract: Laser scanning microscopes can be miniaturized for in vivo imaging by substituting optical microelectromechanical system (MEMS) devices in place of larger components. The emergence of multifunctional active optical devices can support further miniaturization beyond direct component replacement because those active devices enable diffraction-limited performance using simpler optical system designs. In this paper, we propose a catadioptric microscope objective lens that features an integrated MEMS device for per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In the last decade, different approaches to micro electromechanical (MEMS) mirrors have been pursued, mainly depending on the actuation system. Piezoelectric [ 1 ], capacitive [ 2 ], magnetic [ 3 , 4 ], and thermomechanical [ 5 ] actuation mirrors were developed, and their use was demonstrated in a plethora of applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, different approaches to micro electromechanical (MEMS) mirrors have been pursued, mainly depending on the actuation system. Piezoelectric [ 1 ], capacitive [ 2 ], magnetic [ 3 , 4 ], and thermomechanical [ 5 ] actuation mirrors were developed, and their use was demonstrated in a plethora of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the bending-dominated deformation of the lattice cannot fully utilize the load-carrying properties of materials [ 22 , 23 , 24 ]. Additionally, the lattice cores are liable to buckling under compressive loads, while the thick core leads to large spacing between nodes, which weakens the resistance to local panel buckling [ 25 , 26 , 27 ]. Although the development of additive manufacturing has broken the shackles of traditional manufacturing technology and provided opportunities for the production of lattice structures [ 28 , 29 , 30 ], owing to the structural defects and the challenges encountered in traditional manufacturing difficulties, the application of 3D lattice structures in aerospace and aeronautical support structures remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [ 27 ] demonstrated a handheld smartphone fluorescence microscope that can be attached to the smartphone camera for both bright-field and fluorescence imaging at cellular-scale resolutions. Liu et al [ 28 ] proposed a catadioptric microscope objective lens that features an integrated MEMS device for performing biaxial scanning, axial focus adjustment, and control of spherical aberration. In addition, various advances have been made in improving the imaging resolution [ 29 , 30 , 31 ], enhancing the sensitivity of the sensors [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%